An illustrated guide for characters and terminology used in descriptions of Phlebotominae (Diptera, Psychodidae) - Galati Eunice A. B.; Galvis-Ovallos Fredy; Lawyer Phillip; Léger Nicole; Depaquit Jérôme (Parasite, 2017)
Phlebotomine (Diptera, Psychodidae, Phlebotominae) taxonomy has been studied extensively, primarily due to the role of these flies as vectors of various parasites, including species of Leishmania, Bartonella and arboviruses that cause diseases in humans and other vertebrates. We present some topics discussed at a round-table on phlebotomine taxonomy held at the Ninth International Symposium on Phlebotomine Sandflies (ISOPS IX) in Reims, France, in June 2016. To date, approximately one thousand phlebotomine species have been described worldwide, although in varying languages and mostly without standardization of characters and terminology. In the interest of standardization, we list the characters that should minimally be considered in the description of new phlebotomine taxa as well as annotated illustrations of several characters. For these characters, multiple illustrations are provided to show some of the variations. The preferred terms for all pertinent characters are listed as well as their synonyms in English, Portuguese, and French. Finally, we offer an updated list of abbreviations to be used for generic and subgeneric names.